Productivity impact differential of improved rice technology adoption among ricefarming households in Nigeria (2011)
The contribution of technological change to agricultural productivity in developing countries has long been documented. It is believed that the adoption of new agricultural technologies, such as high-yielding varieties, could lead to significant increases in agricultural productivity and stimulate the transition from low-productivity, subsistence agriculture to a high-productivity agro-industrial economy. The article uses the local average treatment effect (fATE) to estimate the impact of adoption of improved rice varieties on rice farmers' productivity in the three major rice ecologies of Nigeria. A stratified random sampling was adopted by the study to select a sample of 500 rice farmers across ecologies. Findings of the analysis indicated that adoption of improved varieties helped raise farmers' area harvested and yield per hectare, respectively, by 0.39 hectare and 21 7.9 kg/ ha for NERTCA and 0.51 hectare and 2.10.4 kg/ ha for other improved varieties, thereby increasing their productivity. In addition, NERICA varieties performed better than any other upland improved variety and the impact of its adoption on both area harvested and yield was greater among female rice farmers than among their male counterparts. Intervention programs to increase the dissemination of high-yielding rice varieties to areas with low productivity are, therefore, a reasonable policy instrument